Psychometric Testing of the CHAMPS Questionnaire in French Canadians with COPD - Susanne Mak; Jean Bourbeau; Nancy E. Mayo; Sharon Wood-Dauphinee; Judith E. Soicher (Canadian Respiratory Journal)
Physical activity is an important health behaviour in reducing morbidity and mortality in individuals with chronic obstructive pulmonary disease (COPD). Accurate measurement of the characteristics of physical activity is essential to understanding the impact of COPD on physical activity. In a previous article, we reported on the cross-cultural adaptation of the Community Healthy Activities Model Program for Seniors (CHAMPS) questionnaire to produce a Canadian French version. The CHAMPS yields four summary scores: two caloric expenditure scores (moderate-intensity activities and all activities) and two frequency scores (moderate-intensity activities and all activities). The objective of this study was to evaluate test-retest reliability and convergent construct validity, in both English and French versions of the CHAMPS, in individuals with COPD. Test-retest reliability was assessed by administering the CHAMPS at two visits (2-3 weeks apart), to 19 English-speaking and 18 French-speaking participants. Validity was assessed in 56 English-speaking and 74 French-speaking participants, who completed the CHAMPS, Short Form- (SF-) 36, and St. George’s Respiratory Questionnaire (SGRQ) at a single visit. Results from reliability testing indicated that intraclass correlation coefficients (ICCs) generally met the threshold for good reliability (ICC > 0.6), with frequency scores showing greater stability than caloric expenditure scores. Validity testing yielded moderate correlations (r = 0.4-0.5) of the CHAMPS with the SF-36 domains and summary score capturing constructs of physical function, and with the SGRQ activity domain and total score. CHAMPS frequency scores for moderate-intensity activities correlated more strongly than other scores, with physical aspects of the SF-36 and SGRQ. The English and French versions of the CHAMPS did not show any substantial differences in reliability (frequency scores) or validity (frequency and caloric expenditure scores). Findings from this study support the reliability and validity of the CHAMPS. In particular, frequency scores for moderate-intensity activities can provide useful information on physical activity levels in individuals with COPD. This trial is registered with NCT00169897. ISRCTN registration number: IRSCTN32824512.